Control of bridge cranes with distributed-mass payloads under windy conditions. (May 2016) - Tang, Rui; Huang, Jie
Abstract: Operating cranes is challenging because payloads experience large and dangerous oscillations, especially when the system is suffering from wind disturbances and the large-size payload is modeled as a distributed-mass model. The payload oscillations induced by both intentional motions commanded by the human operator and by the external wind disturbances make the dynamics more complicated. This paper presents a novel combined control architecture to limit oscillations of the distributed-mass payload caused by both human-operator commands and wind disturbances. While a smoothed command suppressed operator-induced oscillations, a wind-rejection command eliminated the payload swing resulting from the wind gusts. Through simulations, a large range of system parameters and motions are analyzed to investigate the dynamic behavior of bridge cranes with distributed-mass beams and wind disturbances by using the new control scheme. Experimental results obtained from a small-scale bridge crane validate the simulated dynamic behavior and the effectiveness of the proposed method. Highlights: Using a combined scheme to control bridge cranes under windy conditions. The payload states do not need to be measured on-the-fly. Numerous simulations are performed to validate the robustness of the method. Experiments from a crane with distributed-mass beam validate effectiveness.